تأثير الأندلسيين في الجزائر خلال العهد العثماني - مدينة الجزائر نموذجا - - شعشوع مريم; حداد وسام (My University, 2024)
Summary Our study focuses on the indulsians impact in Algeria during the otmanera .The city of Algeria as a simple. Starting from the fall of Granada an the migration of Undalusians, until the settlement in Algeria. Especially the city of Algiers, where the moriscoelement quickly integrated, making significant contributions I the economic, social, cultural and artistic fields, concerning the economic side it was characterized By the use of new agricultural technologies as well as a lot of industries that led to the growth of internal and external trade, while the social aspect was characterised by the transmission of their traditions and customs. In addition to cultural and artistic aspect, the former was marked by the appearance of different scholars who played a great role in making changes at the educational level and building cultural institutions . The latter, was prominent in architecture and andalusion music. ---------------------------------- ملخص يتضمن موضوع دراستنا "تأثير الأندلسيين في الجزائر خلال العهد العثماني –مدينة الجزائر نموذجا- بداية من سقوط غرناطة وهجرة الأندلسيين، وصولا إلى الاستقرار بالجزائر وخصوصا مدينة الجزائر، التي سرعان ما اندمج بها العنصر الموريسكي محدثا إسهامات عديدة في مختلف المجالات الاقتصادية، والاجتماعية،والثقافية، والفنية، فالجانب الاقتصادي تمثل في إدخال تقنيات جديدة خاصة بالزراعة، والعديد من الصناعات المختلفة، التي كان لها الدور في تنشيط حركة التجارة الداخلية والخارجية، أما الجانب الاجتماعي فتمثل في انتقال عاداتهم وتقاليدهم، دون أن ننسى الجانب الثقافي والفني، فالأول كان من خلال بروز العديد من العلماء الذين ساهموا في إحداث تغييرات على مستوى التعليم، وبناء مؤسسات ثقافية، أما الفني فيظهر في العمران والموسيقى الاندلسية. ------------------------------- Résumé Notre étude porte sur l’impacte des indulsiens en algérie à l’époque ottomane La ville d’algérie. Depuis la chute de Grenade et la migration des Undalousiens, jusqu’à l’installation en algérie surtout la ville d’alger, ou l’élément morisco s’est rapidement intégré, apportant des contributions significatives dans les domaines économiques, social, culturel et artistique, concernant le coté économique il s’est caractérisé. Par l’utilisation de nouvelles technologies agricoles ainsi que de nombreuses industries qui ont conduit à la croissance du commerce intérieur et extérieur, tendis que l’aspect social était caractérisé par la transmissions de leurs traditions et coutumes. Outre l’aspect culturel et artistique, la première a été marqué l’apparition de différents savants qui ont joué un grand rôle dans le changement au niveau éducatif et dans la construction d’institutions culturelles. Ce dernier était l’important dans l’architecture et la musique andalouse.
Keywords: الأندلسيين، غرناطة، هجرة، الموريسكي، إسهامات، مجالات(اقتصادية، اجتماعية، ثقافية،فنية)